EU reform: a new treaty of an old constitution - UK. Parliament. House of Commons; Miller, Vaughne (London, 2007)
"Following the failure of all Member States to ratify the 2004 Treaty Establishing a Constitution for Europe, and a 'reflection period' to consider the fate of the treaty, the German EU Presidency in the first half of 2007 relaunched the debate on the future of Europe. It held confidential talks with Member State governments and drew up a Draft Mandate for an Intergovernmental Conference (IGC). The European Council on 21-22 June 2007 agreed the Draft IGC Mandate and the Portuguese Presidency opened the IGC on 23 July, with a view to concluding a new Reform Treaty in October 2007. Many of the Mandate's amendments are articles from the 2004 constitutional text, while others are new and reflect the particular concerns of Member States. When a final amending treaty has been concluded, the ratification process will begin in the 27 Member States. Most Member States will ratify the new treaty by a parliamentary method, although it is likely that those holding a referendum will include Ireland and Denmark. "